Pentingnya Pendidikan Bagi Anak Usia Dini Dalam Membangun Generasi Muslim Berprestasi - Mustar, Mustar; Rahman, Zainur; Hasan, Moh. (STAI Publisistik Thawalib Jakarta, 2022)
Devotion is carried out by guiding early childhood to write Arabic, recognize numbers, recognize body parts and procedures for worship. The guidance method used for early childhood is the Offline method. Offline is a method of implementing work programs that are carried out offline where program implementers visit the location or object where a work program will be implemented. The implementation of the guidance program for early childhood education went well. Although there were several obstacles faced, support from various parties, especially from the institution itself, greatly helped the smooth implementation of the service program in Sumur Dalam hamlet. Education has a positive impact on both children.